상급종합병원 Z세대 간호사의 노인간호실천에 영향을 미치는 요인 - 이아라 (The Graduate School, Ajou University, 2024)
본 연구는 Z세대 간호사의 노인에 대한 지식, 노인돌봄태도, 감성지능과 노인간호실천의 정도를 확인하고 노인간호실천에 영향을 미치는 요인을 파악하기 위한 서술적 상관관계 조사연구이다. 경기도 S시에 소재한 일개 상급종합병원에서 근무하는 경력 6개월 이상의 Z세대 간호사 157명을 대상으로 하였으며, 2023년 9월 5일부터 2023년 9월 13일까지 설문지를 이용하여 자료 수집하였다. 노인에 대한 지식은 Dikken 등(2017)이 개발한 Knowledge about Older Patients Quiz (KOP-Q)를 김은지(2020)가 한국어로 번역한 한국어판 KOP-Q 도구를 사용하였고, 노인돌봄태도는 Sanders, Montgomery, Pittman, & Balkwell(1984)이 개발한 노화의미분별척도와 Maxwell과 Sullivan (1980)이 개발한 Empathy and Attitudies Toward Caring for the Elderly 도구를 기반으로 김영옥(2009)이 개발한 노인돌봄태도 도구를 정혜영(2012)이 수정, 보완한 도구를 사용하였다. 감성지능은 Wong과 Law (2002)가 개발한 Wong and Law Emotional Intelligence scale (WLEIS)을 정하림(2019)이 번안한 한국어판 감성지능 측정도구(K-WLEIS)를 사용하였고, 노인간호실천은 최희자(2002)가 개발한 노인간호실천 도구를 사용하여 측정하였다. 자료 분석은 IBM SPSS 27.0 프로그램을 이용하여 기술통계, Independent t-test, One-way ANOVA, Pearson’s correlation coefficient, Hierarchical regression으로 분석하였다._x000D_ 본 연구의 주요 결과는 다음과 같다._x000D_ _x000D_ 1. 연구 대상자의 노인에 대한 지식은 30점 만점에 평균 21.97점, 노인돌봄태도는 85점 만점에 평균 60.45점, 감성지능은 112점 만점에 평균 81.69점, 노인간호실천은 64점 만점에 평균 51.16점으로 나타났다._x000D_ _x000D_ 2. 연구 대상자의 노인간호실천은 일반적 사항 중 임상단계(F=3.946, p=.021), 조부모 친밀도(F=4.157, p=.017)에 따라 통계적으로 유의한 차이가 있었다. _x000D_ _x000D_ 3. 연구 대상자의 노인에 대한 지식, 노인돌봄태도, 감성지능 및 노인간호실천의 상관관계를 보면, 노인간호실천은 노인돌봄태도(r=.47, p<.001), 감성지능(r=.44, p<.001)과 통계적으로 유의한 양의 상관관계가 있는 것으로 나타났다. _x000D_ _x000D_ 4. 연구 대상자의 노인간호실천에 영향을 미치는 요인을 확인하기 위하여 임상단계와 조부모 친밀도를 통제한 후 2단계 위계적 회귀분석을 실시한 결과, 노인돌봄태도(t=3.50, p<.001)와 감성지능(t=2.46, p=.015)이 노인간호실천에 유의한 영향을 주는 요인으로 나타났다. 노인돌봄태도(β=.31), 감성지능(β=.23)이 높으면 노인간호실천이 증가하였다._x000D_ _x000D_ 따라서 상급종합병원 Z세대 간호사의 노인간호실천 정도를 증진시키기 위하여 노인돌봄태도 및 감성지능 향상을 위한 프로그램 개발이 필요하며, 특히 Z세대의 개인별, 세대별 특성을 고려하여 특성화된 교육과 지지프로그램 개발이 필요하겠다.|This descriptive correlational research aims to determine the level of Generation Z nurses' knowledge about the elderly, attitude toward elderly care, emotional intelligence, and elderly nursing practice, and to identify factors that influence elderly nursing practice. The subjects were 157 Generation Z nurses with more than 6 months of experience working at a tertiary general hospital located in S-si, Gyeonggi-do, and data were collected using a questionnaire from September 5, 2023, to September 13, 2023. Knowledge about the elderly was assessed using the Korean version of the Knowledge about Older Patients Quiz (KOP-Q), developed by Dikken et al. (2017) and translated into Korean by Eunji Kim (2020). Attitude toward elderly care was measured using the tool which was based on Aging Semantic Scale of Sanders, Montgomery, Pittman, & Balkwell (1984) and the Empathy and Attitudies Toward Caring for the Elderly tool of Maxwell & Sullivan (1980), the elderly care attitude tool developed by Kim Young-ok (2009) and modified by Jeong Hye-young (2012). Emotional Intelligence was measured using the Korean version of the Emotional Intelligence Scale (K-WLEIS) by Jeong Ha-Rim, adapted from the Wong and Law Emotional Intelligence Scale (WLEIS) developed by Wong and Law (2002). Elderly nursing practice was measured using the tool developed by Choi Hee-ja (2002). Data analysis was conducted using the IBM SPSS 27.0 program, employing descriptive statistics, independent t-test, one-way ANOVA, Pearson’s correlation coefficient, and hierarchical regression._x000D_ _x000D_ The key findings of this study are summarized as follows:_x000D_ _x000D_ 1. The average score for The knowledge about the elderly was 21.97 points out of 30, attitude toward caring for the elderly was 60.45 points out of 85, emotional intelligence was 81.69 points out of 112, and nursing practice for the elderly was 51.16 points out of 64. _x000D_ _x000D_ 2. There were statistically significant difference in the elderly nursing practice of the study subjects depending on clinical stage (F=3.946, p=.021) and grandparent intimacy (F=4.157, p=.017)._x000D_ _x000D_ 3. Elderly nursing practice showed a statistically significant positive correlation with caring attitude (r=.47, p<.001) and emotional intelligence (r=.44, p<.001) _x000D_ _x000D_ 4. In order to identify factors that affect the study subjects' elderly care practice, a two-stage hierarchical regression analysis was conducted after controlling for clinical stage and grandparent intimacy. As a result, attitude toward elderly care (t=3.50, p<.001) and emotional intelligence (t=2.46, p=.015) were found to be factors that significantly influenced elderly nursing practice. When attitude towards elderly care (β=0.31) and emotional intelligence (β=0.23) were high, the practice of elderly care increased._x000D_ _x000D_ Therefore, in order to improve the level of geriatric nursing practice of Generation Z nurses in tertiary general hospitals, it is necessary to develop programs to improve attitudes toward elderly care and emotional intelligence. In particular, it is necessary to develop specialized education and support programs taking into account the individual and generational characteristics of Generation Z.
학위논문(석사)--간호학과,2024. 2
Keywords: Z세대; 감성지능; 노인간호실천; 노인돌봄태도; 노인에 대한 지식